Konsep Planning dalam Manajemen Pendidikan Islam Menuju Era Society 5.0 - Syahputra, Andri; Afandi, Muslim (Unit Pelaksana Teknis Penelitian dan Pengabdian pada Masyarakat (UPT-P4M) STAI Auliaurrasyidin Tembilahan, 2023)
This article explores the All facets of human life, including education, are currently being affected by the growth of information technology. Three types of literacy are required in the age of the fourth industrial revolution: data literacy, human literacy, and technological literacy. Case-based learning and hybrid/blended learning are both applicable in the revolutionary age 4.0 of education. Even education in the age of society 5.0 allows students to work side by side with robots that are intended to take the place of teachers in learning activities. What about the idea of managing Islamic education inside it, then? In the age of society 5.0, the notion of Islamic education management planning is examined in this essay. As a result, advocates for education management and other interested parties get an understanding of the significance of technology in the era of society 5.0 in the world of education.